(Re)Imagining the nuclear in Lithuania following the shutdown of the Ignalina nuclear power plant. Issue 3 (3rd July 2022) - Dovydaitytė, Linara
ABSTRACT: This article examines public representations of the nuclear in Lithuania following the shutdown of the Soviet-designed Ignalina nuclear power plant. The central focus of the article is the analysis of artistic practices that, since the early 2000s, interpret and transform the materiality of the plant from a nuclear object to a cultural phenomenon. The author argues that while the decommissioning process of the only Lithuanian nuclear power plant occupies a rather marginal place in the popular consciousness, art becomes an increasingly important medium for the construction of nuclear imaginaries attracting public attention and raising awareness of nuclear industry issues.